Meningkatkan Kemampuan Literasi Matematis dengan Pendekatan Metacognitive Guidance Berbantuan GEOGEBRA - Khotimah Khotimah (GAUSS: Jurnal Pendidikan Matematika, 2018)
The purpose of this research was to investigate the effects of Metacognitive Guidance Approach assisted by GeoGebra on mathematical literacy. In particular, the study compares two learning environment: a) conventional learning, and b) metacognitive guidance learning using GeoGebra. This study was carried out on student‟s ability level (low, medium and high ability group), and their competence on mathematical literacy. This research was non equivalent pretest – postest - control group design. The results of data analysis showed that: 1.a) the students who were exposed to MG+GeoGebra outperform students that were not exposed to MG+GeoGebra on mathematical literacy; 1.b) the students in high and medium ability group who were exposed to MG+GeoGebra outperform students that were not exposed to MG+GeoGebra on mathematical literacy; 2) there was no interaction between learning method and student‟s ability level on mathematical literacy.